PRC2 targeting is a therapeutic strategy for EZ score defined high-risk multiple myeloma patients and overcome resistance to IMiDs - Herviou, Laurie; Kassambara, Alboukadel; Boireau, Stéphanie; Robert, Nicolas; Requirand, Guilhem; Müller-Tidow, Carsten; Vincent, Laure; Seckinger, Anja; Goldschmidt, Hartmut; Cartron, Guillaume; Hose, Dirk; Cavalli, Giacomo; et al. (Clinical epigenetics, 2018)
Multiple myeloma (MM) is a malignant plasma cell disease with a poor survival, characterized by the accumulation of myeloma cells (MMCs) within the bone marrow. Epigenetic modifications in MM are associated not only with cancer development and progression, but also with drug resistance.